Realizing Smart City Infrastructure at Scale, in the Wild: A Case Study - James, Philip; Jonczyk, Jennine; Smith, Luke; Harris, Neil; Komar, Tom; Bell, Daniel; Ranjan, Rajiv (Frontiers in Sustainable Cities, 2022)
The smart city term has been widely used for a number of years and many pilot projects and limited scale, sector independent initiatives have been progressed, but comprehensive, long-term, city wide, multi-sector systems are much less evident. This paper examines one such case study in Newcastle, UK highlighting the challenges and opportunities that realising "smart city" concepts at scale present. The paper provides the background to the Newcastle Urban Observatory project and discusses the socio-technical and practical challenges of developing and maintaining smart city networks of sensors in the plurality that is a modern city. We discuss the organisational requirements, governance, data quality and volume issues, big data management and discuss the current and future needs of decision makers and other city stakeholders. Finally, we propose areas where smart cities can have a positive impact on public outcomes through the discussion of two case studies related to COVID-19 and pedestrianisation initiatives.